Distribution of bed material in a Horizontal Circulating Fluidised Bed boiler - Ekvall, Thomas; Magnusson, Robin (My University, 2011)
A conventional circulating fluidised bed (CFB) boiler has a limitation due to the height of the furnace, when implemented in smaller industrial facilities. The design of a horizontal circulating fluidised bed (HCFB) boiler is an interesting approach to resolve this problem. Enabling the benefits, such as high efficiency and fuel flexibility, of the CFB technology for the use in smaller industrial facilities decreases the carbon dioxide emissions tremendously,especially in a country like China. The purpose of this work is to investigate how a HCFB boiler responds to change in fluidisation velocity and bed mass respectively. The tests are mainly performed using a cold HCFB model and are complemented with tests on an industrial HCFB boiler. The industrial boiler is located at Kings Paper in Xiamen, China, supplying steam to the paper machine. The result from the cold HCFB model shows an uneven distribution of bed material over the cross sectional area in the 2nd chamber. The distribution of the bed material affect the heat transfer to the tubing walls within the boiler. Uneven distribution of particles will not result in a highest possible heat transfer, thus will affect the efficiency of the boiler. By making a comparison to the classical CFB, this work shows that the cyclone load is much lower in a HCFB. The cyclone load is an important parameter concerning investment costs. The classical CFB design in this report is represented by the CFB boiler located at Chalmers University of Technology, Gothenburg, Sweden.
Keywords: Energi; Hållbar utveckling; Energiteknik; Miljöteknik; Energy; Sustainable Development; Energy Engineering; Environmental engineering